Pemahaman Nazhir dan Penerapan Sistem Akuntansi Wakaf Berdasarkan PSAK 112 - Kautsar Riza Salman; Aziz Fadillah Mukadar (ITB AAS INDONESIA Surakarta, 2022)
This study focuses on waqf, which specifically analyzes the waqf accounting system based on the PSAK that DSAS just approved in early 2021. This study aims to determine Nazhir's understanding of applying the waqf accounting system based on PSAK 112 at waqf management institutions in the Surabaya area. The sampling technique in this study used snowball sampling and data collection methods utilizing observation, interviews and documentation. This study used four nazir informants from waqf management institutions in the Surabaya area. The method used in this research is descriptive qualitative. This research focuses on the unit of analysis of the understanding and application of nazir based on PSAK 112. The results of this study nazir in understanding and applying this standard are divided into two. BMT Sri Sejahtera and Nurul Hayat Foundation do not understand this PSAK 112. The second is BMT Amanah Ummah and Nazir Universitas Airlangga, who has understood and applied PSAK 112 seen from the latest reports by PSAK 112 and statements of interview results.